Modified subgradient extragradient algorithms for variational inequality problems and fixed point problems. (2nd January 2018) - Thong, Duong Viet; Hieu, Dang Van
Abstract: The subgradient extragradient method can be considered as an improvement of the extragradient method for variational inequality problems for the class of monotone and Lipschitz continuous mappings. In this paper, we propose two new algorithms as combination between the subgradient extragradient method and Mann-like method for finding a common element of the solution set of a variational inequality and the fixed point set of a demicontractive mapping.